Ship construction for marine engineers - Russell, Paul Anthony (Reeds marine engineering and technology series, 2016)
This textbook covers ship construction techniques and methods for all classes of Merchant Navy marine deck and engineering Certificates of Competency (CoC) as well as undergraduate students studying Naval Architecture and Marine Engineering. Importantly, this new edition contains up-to-date information on modern shipyards, dry-docking procedures and methods of construction. Extensively illustrated, the book also includes sample examination questions with worked example answers to aid students in their learning. It takes into account the varying needs of marine students, recognising recent changes to the Merchant Navy syllabus and current pathways to a sea-going career as a ship's officer, including National Diplomas, Higher National Diploma and degree courses.